2023
DOI: 10.5812/jkums-136995
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Social Problem-Solving Skills Training on the Depression in Systolic Heart Failure Patients in Kermanshah

Abstract: Background: Heart failure is common worldwide, and it is still expanding. Psychological factors such as depression are more effective on the consequences of this disease, which is necessary to seek a solution for controlling. Objectives: This study aimed to investigate the effect of social problem-solving skills training (SPSST) on depression in patients with heart failure. Methods: This semi-experimental study was conducted on two groups of ten male patients with heart failure in Kermanshah, Iran, randomly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…For example, Thoma et al showed that teaching social problem-solving skills was effective in treating mental disorders (30). Also, the results of the studies of Omidi et al showed the effect of teaching SPSST on anxiety, sleep quality, and depression in heart patients (31,32). Another study showed the effect of short-term training of…”
Section: Discussionmentioning
confidence: 99%
“…For example, Thoma et al showed that teaching social problem-solving skills was effective in treating mental disorders (30). Also, the results of the studies of Omidi et al showed the effect of teaching SPSST on anxiety, sleep quality, and depression in heart patients (31,32). Another study showed the effect of short-term training of…”
Section: Discussionmentioning
confidence: 99%